Semen inhibits Zika virus infection of cells and tissues from the anogenital region - Müller, Janis-Alexander; Cortese, Mirko; Bartenschlager, Ralf (Nature Communications, 2018)
Semen from Zika virus infected individuals can contain high viral loads and can result in sexual transmission. Here, Müller et al. show that semen, and particularly seminal preparations containing extracellular vesicles, inhibit infection of Zika and other flaviviruses.
Gesehen am 09.05.2019